Perilaku Kolektif dalam Menghadapi Bencana: Akidah dan Kebersamaan - Najamudin Najamudin; Surahman Hidayat (Prosiding Seminar Nasional Ilmu Pendidikan Agama dan Filsafat, 2024)
Active behavior in facing disasters plays a crucial role in reducing the impact and accelerating the recovery process. This study aims to explore the relationship between aqidah (religious beliefs) and togetherness in shaping the collective response of society to disasters. Using a qualitative approach, this study analyzes data from field observations and interviews with various community groups affected by natural disasters in Indonesia. The results of the study indicate that religion can be a social capital, and has the values ​​and norms of monotheism, patience, sincerity, tawakkal and togetherness and shows that strong aqidah can increase the spirit of togetherness and mutual cooperation, which contributes to reducing anxiety and accelerating aid and recovery. This study concludes that collective behavior built on religious values ​​and togetherness can strengthen the social resilience of society in facing disasters.